EFEK BULLYING TERHADAP KETERAMPILAN KOMUNIKASI PADA REMAJA AWAL DI KOTA SURAKARTA: REGRESI LOGISTIC MULTILEVEL DARI SURAKARTA JAWA TENGAH - Sudrajad, Kiyat (Medical Journal of Nusantara, 2023)
Background. Human interaction requires communication as a transmission of information, ideas, emotions, skills, and so on. Communication occurs when a source conveys a message to the recipient with a conscious intention to influence the recipient's behavior. One of the problems in social communication is bullying. Bullying or harassment can be through words or through actions that aim to make the opponent's mental fall and pressure. The purpose of this study was to analyze the factors that influence bullying against depression with the Health Belief Model and Social Cognitive Theory. Subjects and Method. This was a cross-sectional study conducted in junior high schools in Surakarta, in September 2023. A total sample of 250 adolescents was selected by simple random sampling. The dependent variable was bullying. The independent variables were perceived susceptibility, perceived severity, cues to action, perceived threat, perceived benefit, perceived barrier, self-efficacy, and communication. The data were collected by questionnaire and analyzed by a multiplemultilevel logistic regression run on Stata 13. Results. Bullying increased poorcommunication (b= 4.95; 95% CI= 2.24 to 10.89; p <0.001). Conclusion. Bullying increases poor communication.